2014
DOI: 10.1007/s10461-014-0831-y
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Evidence of Harm from Self-Tests

Abstract: Although HIV self-testing may overcome some barriers to HIV testing, various stakeholders have expressed concerns that HIV self-testing may lead to unintended harm, including psychological, social and medical harm. Recognizing that similar concerns were raised in the past for some other self-tests, we conduct a review of the literature on a set of self-tests that share some characteristics with HIV self-tests to determine whether there is any evidence of harm. We find that although the potential for harm is di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 28 publications
6
66
2
Order By: Relevance
“…If the introduction of self-testing kits did lead to such harm, this could constitute a strong objection to them. However, as we have noted earlier, there is little evidence to support this fear 12 22. That said, it would be prudent to monitor for such behaviour now that self-testing kits are available.…”
Section: The Result: Reactivementioning
confidence: 90%
See 1 more Smart Citation
“…If the introduction of self-testing kits did lead to such harm, this could constitute a strong objection to them. However, as we have noted earlier, there is little evidence to support this fear 12 22. That said, it would be prudent to monitor for such behaviour now that self-testing kits are available.…”
Section: The Result: Reactivementioning
confidence: 90%
“…People increasingly understand that HIV is a chronic condition, and society is far more accepting than it used to be of those afflicted by the virus 17. As such, evidence suggests that the risk of serious psychological harm from self-testing is now low 22. It is also worth noting that some scholars have thought it implausible to suggest that a short pretest counselling session could significantly dampen the psychological impact of a reactive HIV result 14.…”
Section: Before the Testmentioning
confidence: 99%
“…As a result, women were able to overcome the initial fears and successfully delivered the kits to their male partners with no serious adverse events reported. Indeed, a review of the evidence of harm from HIV self-tests found that although the potential for harm is discussed in the literature on self-tests, there is very little evidence that such harm occurs [20]. Collectively, our findings and findings from previous studies suggest that women can safely deliver HIV self-test kits to their male partners, and this, in itself, can help to improve HIV-testing rates in men, which is important for identifying HIV-positive men at an early stage in order to link them to appropriate HIV care and treatment services.…”
Section: Discussionmentioning
confidence: 99%
“…Access to HIV testing permits infected individuals to receive early treatment, thus increasing survival rates and reducing morbidity and mortality associated with the virus (16,17). Furthermore, the knowledge of serological status contributes to reducing risk behaviors and viral transmission (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the knowledge of serological status contributes to reducing risk behaviors and viral transmission (17,18). The rate of HIV transmission is estimated to be 3.5 times greater among individuals who are unaware of their serologic status (19).…”
Section: Introductionmentioning
confidence: 99%